Conocemos los primeros pobladores del Perú - Villena Aguilar, Ruth Mery (2018)
Through the development of this Learning Session it is intended that the student obtain the necessary information so that they can build historical interpretations in which they recognize that the present is a consequence of a set of social dynamics that were developed simultaneously in the past and that the actions of the various social actors have consequences in the future. Also know and explain in a general way, Peruvian historical processes, as well as the consequences whose effects are seen immediately or in the long term and can chronologically order Peruvian historical processes.